The short reign of Pippin IV : a fabrication - Steinbeck, John, 1902-1968 (Viking Press, 1957)
A satire on French politics follows the fate of amateur astronomer Pippin Heristal after he is drafted to rule the unruly French. Bored, Pippin is instrumental in starting a revolution.